2008
DOI: 10.1002/hpm.949
|View full text |Cite
|
Sign up to set email alerts
|

Access to essential drugs in Guyana: a public health challenge

Abstract: Guyana's pharmaceutical sector faces major challenges that limit access to essential drugs. This study analyzes Guyana's drug policy and regulation, public financing, and drug procurement and delivery. The study also identifies main barriers to drug access and proposes alternatives to strengthen the country's public health functions. Data were collected from the country's regulatory agencies, public procurement agency, pharmacies, wholesalers, and pharmaceutical companies. The information was supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Historical series of expenditures of federated entities in Brazil [24, 28] and comparisons between specifics programs [29] provided an overview of public purchase. Some papers focused on the organization of public financing, as well as the acquisition and distribution chain in Brazil [30] and in other countries such as Guyana [16]. Price comparison of generic oncological medicines was central in an article from Colombia [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historical series of expenditures of federated entities in Brazil [24, 28] and comparisons between specifics programs [29] provided an overview of public purchase. Some papers focused on the organization of public financing, as well as the acquisition and distribution chain in Brazil [30] and in other countries such as Guyana [16]. Price comparison of generic oncological medicines was central in an article from Colombia [27].…”
Section: Resultsmentioning
confidence: 99%
“…Most articles in this category referred to Brazil (80.8%) [12, 13, 15, 1725, 2830, 32–37] but they also included Argentina [14], Guyana [16], Chile, Colombia [26, 27] and Ecuador [31].…”
Section: Resultsmentioning
confidence: 99%
“…But a divergent finding was obtained from a study in Brazil which found weaknesses in local selection procedures and in the use of the National essential medicines lists [16]. Similarly, another study in Guyana and Brazil found weaknesses in the selection process of essential drugs [16,17]. About 58% of the primary health care centres had average availability of essential drugs while the remaining 42% had poor availability of essential drugs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This combination of factors relegates real-world access to a function of grassroots efforts by providers, patients and local communities, with resultant inefficiencies and inequities as documented in other LMIC contexts. [38][39][40] The interconnectivity across sectors, actors and system levels reveals what Atun 41 refers to as 'dynamic complexity'; such interconnectivities warrant greater attention in policy development and implementation.…”
Section: Discussionmentioning
confidence: 99%